Phase composition and property evolution of (Yb1−xHox)2Si2O7 solid solution as environmental/thermal barrier coating candidates. Issue 10 (August 2022) - Lv, Xirui; Cui, Jingping; Zhang, Jie; Wang, Jingyang
Abstract: RE disilicates are good candidates as environmental/thermal barrier coating for SiCf /SiC composite in harsh gas turbine engines. We designed (Yb1−x Hox )2 Si2 O7 solid solutions and studied mechanical properties, thermal properties, and water vapor resistance. Powders with different compositions were synthesized by pressureless sintering, and bulk samples were prepared by Spark Plasma Sintering (SPS). Polymorphic changes with temperature and composition of the solid solutions were examined. Through doping Ho into Yb2 Si2 O7, water vapor corrosion resistance is significantly promoted, and thermal expansion coefficient is maintained close to that of Si-based ceramics. Compared with host disilicates, thermal conductivity of solid solutions are decreased, and mechanical properties, including Vickers hardness and fracture toughness, are increased. A two-phase domain is found at (Yb1/2 Ho1/2 )2 Si2 O7, and the γ to δ phase transition of Ho2 Si2 O7 is observed during SPS. Among all samples, γ-(Yb1/3 Ho2/3 )2 Si2 O7 possesses superior high temperature stability, and excellent water vapor resistance, indicating its performance as environmental/thermal barrier coating.